Spatial policy and planning in Northern Europe: an assessment of recent trends in policy and economic development - Andreas P. Cornett; Frank Othengrafen (European Regional Science Association (ERSA), 2010)
Spatial aspects of economic and social cohesion have become a major target in European policy in the last decades. By combining the structural funds with spatial development perspectives, the recently introduced concept of territorial cohesion obviously functions as link between EU regional policy and spatial development. In other terms, territorial cohesion should be considered as an umbrella concept complementing and reinforcing economic and social cohesion. The purpose of the paper thus is twofold. First, it is the aim to analyze briefly the socio-economic background and the changes in the regional economic structure of the EU, partly as a result of socio-economic changes, partly as a consequence of the enlargement from 15 predominantly wealthy mature marked economies with 12 transition economies and two small Mediterranean states. The first section also provides (1) a brief outline of the history and the political foundations of the emergence of the EU regional policy in the aftermath of the first attempts to create an Economic and Monetary Union; and (2) an analysis of the main trends in European economic convergence and disparities to provide empirical evidence why the issue has climbed upwards on the political agenda in the last decade. The second purpose is then to analyze the added value (if there is any) of the concept of territorial cohesion for economic and social convergence by providing an analytical overview of the changes in the spatial agenda from European spatial planning -starting in the 1970's with the establishment of the CEMAT by the European Council - to territorial cohesion and its implications for the EU regional policy. Furthermore, the paper discusses the recent attempts to integrate the issues of economic, social and territorial cohesion in the EU cohesion policy 2007-13 and the Lisbon Treaty on the reform of European Union. This section also analyzes the altered balance between the European and the national level with regard to spatial and territorial issues. The final section of the paper summarizes the main findings with special attention on the North European context.
Keywords: 330; Territorial cohesion and cooperation; economic convergence; multilevel governance